PERSEPSI WAJIB PAJAK TERHADAP CITRA PERPAJAKAN INDONESIA SETELAH FENOMENA KASUS KORUPSI PAJAK - Dian Purnama Sari (STIE Malangkucecwara, 2020)
This study aims to understand the perception of taxpayers after corruption cases involving tax officials in Indonesia. This research uses Mixed Method. Beginning with the PLS test which shows that perceptions of taxpayers have a negative effect on taxpayer obedience. Furthermore, phenomenology is used to further reveal taxpayer compliance. The result there are 3 understandings, namely (1) The image of Indonesian taxation has deteriorated, such as